A finite difference method for the solution of electromagnetic waveguide discontinuity problems - Mur, G (IEEE transactions on microwave theory and techniques, 1974)
A finite-difference method for the numerical solution of electromagnetic waveguide discontinuity problems is presented. The method of boundary relaxation is applied, using finite-difference techniques in the nonuniform section of the waveguide and using a modal representation of the field in the uniform sections of the waveguide. To illustrate the process, some two-dimensional diffraction problems in an electromagnetic waveguide with rectangular cross section are solved.